2017
DOI: 10.1038/s41598-017-13490-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and physiological relevance of designing highly potent aminopeptidase-sparing leukotriene A4 hydrolase inhibitors

Abstract: Leukotriene A4 Hydrolase (LTA4H) is a bifunctional zinc metalloenzyme that comprises both epoxide hydrolase and aminopeptidase activity, exerted by two overlapping catalytic sites. The epoxide hydrolase function of the enzyme catalyzes the biosynthesis of the pro-inflammatory lipid mediator leukotriene (LT) B4. Recent literature suggests that the aminopeptidase function of LTA4H is responsible for degradation of the tripeptide Pro-Gly-Pro (PGP) for which neutrophil chemotactic activity has been postulated. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Within our article, we provided a compelling case that accumulation of PGP could drive pathological epithelial remodeling that in turn exacerbates airway resistance. Leukotriene A 4 hydrolase (LTA 4 H)-deficient mice exposed to house dust mite (HDM) demonstrated an accumulation of PGP, supporting our previous studies that unequivocally demonstrated that LTA 4 H was the only enzyme of physiological relevance that degrades PGP and that the peptide accumulated in its absence (3)-findings corroborated by some of the authors of the Technical Comment (4). In the context of our allergic airways disease model, this accumulation of PGP resulted in a profound increase in epithelial height and mucus production, despite markers of T helper 2 (T H 2) inflammation being substantially reduced [as a consequence of loss of leukotriene B 4 (LTB 4 )].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Within our article, we provided a compelling case that accumulation of PGP could drive pathological epithelial remodeling that in turn exacerbates airway resistance. Leukotriene A 4 hydrolase (LTA 4 H)-deficient mice exposed to house dust mite (HDM) demonstrated an accumulation of PGP, supporting our previous studies that unequivocally demonstrated that LTA 4 H was the only enzyme of physiological relevance that degrades PGP and that the peptide accumulated in its absence (3)-findings corroborated by some of the authors of the Technical Comment (4). In the context of our allergic airways disease model, this accumulation of PGP resulted in a profound increase in epithelial height and mucus production, despite markers of T helper 2 (T H 2) inflammation being substantially reduced [as a consequence of loss of leukotriene B 4 (LTB 4 )].…”
supporting
confidence: 84%
“…Leukotriene A 4 hydrolase (LTA 4 H)-deficient mice exposed to house dust mite (HDM) demonstrated an accumulation of PGP, supporting our previous studies that unequivocally demonstrated that LTA 4 H was the only enzyme of physiological relevance that degrades PGP and that the peptide accumulated in its absence (3)-findings corroborated by some of the authors of the Technical Comment (4). In the context of our allergic airways disease model, this accumulation of PGP resulted in a profound increase in epithelial height and mucus production, despite markers of T helper 2 (T H 2) inflammation being substantially reduced [as a consequence of loss of leukotriene B 4 (LTB 4 )]. Subsequently, neutralization of PGP within our model abolished this epithelial phenotype, whereas direct application of acetylated PGP (AcPGP) (a more stable derivative of PGP) onto human bronchial epithelial cells at airway liquid interface directly replicated the in vivo phenotype.…”
supporting
confidence: 84%
“…Recently, a new compound, ARM1 (4‐[4‐(phenylmethyl)phenyl]‐2‐thiazolamine), was shown to selectively inhibit LTA4F EH activity but spares the AP activity of LTA4H . It was also reported that ARM1 does not selectively inhibit LTA4H EH activity …”
Section: Lta4h As a Target Of Cancer Prevention And Therapymentioning
confidence: 99%
“…A recent study by Numao et al reported that PGP does not induce neutrophil influx in a murine model and does not stimulate human neutrophils in vitro. 31 Further studies are needed to determine how LTA4H precisely controls EH activity toward LTB4 and AP activity toward PGP. Important findings related to LTA4H and its biological functions are presented in Figure 1.…”
Section: Historical Achievements In Lta4h Researchmentioning
confidence: 99%
See 1 more Smart Citation